ANALISIS MATURITAS SISTEM PENGENDALIAN INTERN PEMERINTAH PADA PEMERINTAH KOTA PEKANBARU - Ariesty Ariesty; Ria Nelly Sari; M Rasuli (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2021)
This study aims to analyze the implementation of the Government Internal Control System (GICS) in the city government of Pekanbaru. This research is a qualitative research with a case study approach and a Soft System methodology in problem solving. The data collection technique in this research is by conducting in-depth interviews, observation and documentation. The results showed that GICS for Pekanbaru City had been implemented in accordance with Government Regulation Number 60 of 2008. SPIP for Pekanbaru City was already at level 3 (three) but there were obstacles in its implementation, namely lack of commitment, lack of understanding of GICS, disorderly filing of documents, mutations or the frequent turnover of employees in the Pekanbaru City Government, insufficient human resource competence, limited budgets. Efforts made to overcome the obstacles in implementing GICS are compiling, implementing and evaluating SOP activities as well as disseminating information to related parties, order filing documents for each activity , conduct socialization and technical guidance for all regional officials, carry out education and training for assessors, carry out consultations, improve performance and commitment with respect for achievement. This study has a contribution to the Pekanbaru city government in increasing the maturity level of its internal control system.